Italy : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2002)
This Report on the Observance of Standards and Codes (ROSC) data module provides a review of Italy's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS), complemented by an in-depth assessment of the quality of national accounts, consumer price index, producer price index, government finance, monetary, and balance-of-payments statistics. The assessment reveals that Italy subscribes to the SDDS. It also meets the SDDS specifications for coverage, periodicity, and timeliness for all data categories (with two exceptions) and for advance release calendars.